The impacts of climatic conditions on dengue fever and general emergency hospital admissions in tropical Indonesia - Asiga Cahya Adhianti Rosa; Kubota Tetsu; Putra Pradana Radyan; Soo Lee Han (E3S Web of Conferences, 2023)
Changes in climate parameters such as air temperature, rainfall, and humidity may dramatically impact the occurrence of infectious diseases. Dengue fever is a prevalent disease that has been extensively reported in relatio to climate change, particularly in tropical countries such as Indonesia. In addition, the consequences of climate change may affect the physiological responses of our bodies, which could lead to a rise in hospital admissions even in tropical countries. Wet Bulb Globe Temperature (WBGT) is an index to estimate the effect of air temperature, humidity, and solar radiation on human bodies. First, this study aims to investigate the influence of climatic conditions, including air temperature (AT), relative humidity (RH), and rainfall (RF), on the occurrence of dengue fever in Jakarta, Bandung, and Malang city, through a cross-correlation analysis. Second, it also explains the relationships between WBGT and general emergency hospital admissions in Indonesia and Japan. The results showed that climate conditions such as rainfall and humidity had a strong correlation with the incidence of dengue in Indonesia, with a relatively short lag of around 2-5 months in the form of negative values, while positive values were observed with a lag of 9-10 months with some exceptions in Jakarta. Extreme WBGT changes do not affect general emergency hospital admissions in both Hiroshima and Indonesian cities, although the WBGT changes clearly affected the emergency hospital admissions caused by the heat stroke in Hiroshima.